2014
DOI: 10.1590/s1516-05722014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Influência da adubação com nitrogênio e fósforo na produção de Jambu, Acmella oleracea (L) R.K. Jansen

Abstract: RESUMO:Com o objetivo de avaliar a influência de doses de nitrogênio e fósforo na cultura do Jambu, foi instalado experimento na fazenda experimental da APTA Polo Vale do Ribeira utilizando-se sementes da cultivar Nazaré. Os tratamentos foram conduzidos em blocos casualizados em esquema fatorial 4 x 4, e quatro repetições dos seguintes tratamentos: quatro doses de nitrogênio, (0; 37,5; 75 e 112,5 kg ha -1 N), quatro doses de fósforo (0; 75; 150 e 300 Kg ha -1 de P 2 O 5 ). O solo foi inicialmente preparado rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
3
10
0
7
Order By: Relevance
“…The productivity of the accessions of Purple Flower and Yellow Flower jambu were 2.29 and 2.38 kg m -2 , respectively. These values were within the range of average values of the state of Pará, which is 1.8 to 3.0 kg m -2 according to Rodrigues et al (2014).…”
Section: Growth Curves and Nutrient Absorptionsupporting
confidence: 72%
“…The productivity of the accessions of Purple Flower and Yellow Flower jambu were 2.29 and 2.38 kg m -2 , respectively. These values were within the range of average values of the state of Pará, which is 1.8 to 3.0 kg m -2 according to Rodrigues et al (2014).…”
Section: Growth Curves and Nutrient Absorptionsupporting
confidence: 72%
“…The result of fresh matter found in this study presented behavior similar to that found by Silva et al (2013), who worked with beet under different soil-water stresses and found a linear model for fresh matter production, with a maximum value at stress closer to field capacity (15 kPa). Rodrigues et al (2014) evaluated the influence of nitrogen and phosphorus fertilization on jambu production and found maximum fresh matter production (leaves and flowers) of 4,012.4 g m 2 at a dose of 112.5 kg ha −1 of nitrogen. These results confirm that water and nutrient availability is fundamental for the increase of fresh matter in jambu.…”
Section: Resultsmentioning
confidence: 99%
“…Leafy vegetables have a direct effect of nitrogen on plant growth and, consequently, productivity (Mota et al, 2016;Rezende et al, 2017;Farias et al, 2015;Vieira Filho et al, 2017). Rodrigues et al (2014) found a significant difference of jambu production in Pariqueira-Açu, São Paulo, Brazil, as a function of nitrogen doses; the treatment with the highest dose showed a 90% increase for fresh matter production in relation to the treatment with the total omission of this element. Borges et al (2014) analyzed the productivity of jambu cultivars influenced by organic and mineral fertilization and found maximum values of 2.98 kg m 2 using mineral fertilizer at a dose of 69.9 g m 2 of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Considerado uma hortaliça folhosa, o jambu tem conquistado inúmeros consumidores por apresentar propriedades peculiares, sendo a mais importante a sensação anestésica momentânea, ocasionada pelo consumo de suas partes vegetativas (Homma et al, 2014). Devido a essa propriedade, o jambu alcançou lugar de destaque na culinária do Brasil, além de ser considerado uma erva medicinal pela população ribeirinha, que utiliza seus preparados para o tratamento de dor de dente e moléstias da garganta (Rodrigues et al, 2014).…”
Section: Introductionunclassified